1986
DOI: 10.2105/ajph.76.6.638
|View full text |Cite
|
Sign up to set email alerts
|

Distributional change in physician manpower, United States, 1963-80.

Abstract: Using data from the American Medical Association's Physician Masterfiles and the GINI index of resource concentration as a global measure of changes in the pattern of locational choice, the expectation of a more uniform distribution of physicians is shown to have been met for all major categories of physicians except General Practitioners. Increases in the supply of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Limiting our operational definition to respondents' reports of problems obtaining needed care may have underestimated the importance of health system resources, for example. While we acknowledge access as a multidimensional concept [57], our findings are consistent with several studies examining indicators of realized access or use of a broad range health care services [37,57,[60][61][62][63][64][65][66][67][68]. Third, unreliable or invalid measures of health system resources may have resulted in missed associations.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Limiting our operational definition to respondents' reports of problems obtaining needed care may have underestimated the importance of health system resources, for example. While we acknowledge access as a multidimensional concept [57], our findings are consistent with several studies examining indicators of realized access or use of a broad range health care services [37,57,[60][61][62][63][64][65][66][67][68]. Third, unreliable or invalid measures of health system resources may have resulted in missed associations.…”
Section: Discussionsupporting
confidence: 85%
“…Previous work has also attempted to develop mathematical models that identify under-served areas so that resources can be more readily deployed [47]. Despite this attention, evidence in recent years suggests that inequities in the distribution of health system resources and their use persists [37,57,[60][61][62][63][64][65][66][67][68]. Some have concluded that these efforts may have failed because they did not consider social or economic factors that contribute in potentially important ways to the difficulties residents encounter in accessing health care in the face of an apparently adequate supply of health care providers [51].…”
Section: Discussionmentioning
confidence: 99%
“…Its value lies between 0 (no inequality) and 1 (complete inequality). These methods have been applied for studying the equal distribution of physicians [1,2,7,24-26]. …”
Section: Methodsmentioning
confidence: 99%
“…In the United States, empirical investigations into whether the geographic distribution of physicians has deteriorated or improved over time have tended to use the same methodological approach: namely, the Gini index of resource concentration. For example, the Gini index methodology has been employed by Politzer, Cultice and Meltzer (1998), Ricketts, Gesler andOsborne (1994), andMcConnel andTobias (1986). The index has been found to adequately and sensitively measure the degree of difference between two distributions.…”
Section: Methods and Datamentioning
confidence: 99%